Comparative study of endometrial thickness with transabdominal ultrasonography and pelvis in perimenopausal women presenting with abnormal uterine bleeding and correlation with its histopathological findings - D., Rita; Sourya K. A. , Pallavi; A., Lathasri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Heavy menstrual bleeding is the most common presenting menstrual complaint in women of perimenopausal age group. Diagnostics tests to investigate the causes of abnormal bleeding are transabdominal ultrasonography (TAS), TVS, endometrial biopsy and uterine curettage which is invasive procedure performed under anesthesia. The objectives of this study were to correlate the transabdominal ultrasonography results with the histopathological findings to discriminate normal from pathological endometrium. Methods: Comparative study including 100 perimenopausal women with abnormal uterine bleeding. Endometrial thickness was measured by TAS and then D and C was performed for all the patients. Results: Out of 100 women, (86) had normal and (14) had an abnormal endometrium. 43 were of 41-45 years and 65 patients presented with complaint of heavy menstrual bleeding. Fibroid uterus (24%) was the commonest uterine pathology detected on TAS. 53 of patients had endometrial thickness in the range 10-11.9 mm. Most common finding on HPE was secretory endometrium (44). Endometrial carcinoma was found in 1. Endometrial thickness <12mm was associated with least abnormal endometrial pathology. Conclusions: Irrespective of endometrial thickness all perimenopausal women with HMB should be subjected to TAS followed by D and C which helps in early detection and missing out of endometrial carcinoma.